(untitled) (Nóema, 2022)
The everyday sense of pragmatic involves ideas of sensible practice, cautious realism about current situations, flexibility allied to technical knowledge, and the prioritisation of what works, as opposed to unrealistic and damaging ideals. I argue against this technical and sensible flavour of pragmatism, pre-sent in many of its historical and contemporary versions. Pragmatism can be taken as technically-minded, realistic and practical, thereby avoiding the excesses of abstract ideologies. Instead, I will defend the thesis that pragmatism should be fantastic, in the precise sense of metaphysically inventive. In making this latter argument, my main critical point will be against the metaphysically «quietist» version of pragmatism, in particular as defended by David Macarthur. My claim is counter-intuitive, since it seems to commit pragmatism to the forms of idealism that it has sought to criticise and escape. If metaphysics propose ideal pictures of the world, as opposed to detailed, local and evidence-based descriptions - allied to rigorous experimentation - then the fantasies of metaphysics are exactly what pragmatism should avoid. In response to this critical counter, I will argue that pragmatism should be metaphysically inventive because it cannot avoid being metaphysical. However, I also argue that it should be self-critical in its fantastic creativity.